A SECRET SHARING SCHEME BASED ON MULTIVARIATE POLYNOMIALS - Ari Dwi Hartanto; Sutjijana Sutjijana (Journal of Fundamental Mathematics and Applications (JFMA), 2019)
A Secret sharing scheme is a method for dividing a secret into several partialinformation. The secret can be reconstructed if a certain number of partial information is collected. One of the known secret sharing schemes is the Shamir’s secret sharing scheme. It uses Lagrange interpolation (with one indeterminate) for reconstructing the secret. In this paper, we present a secret sharing scheme using multivariate polynomials with the secret reconstruction process using the multivariate interpolation formula derived by Saniee (2007). The resulted scheme can be considered as a generalization of the Shamir’s secret sharing scheme.